CROSS-COUNTRY MANGROVE CONSERVATION: SYNERGY OF PUI MANGROVE USU AND PUI UNPRI SPATIAL DEVELOPMENT IN THE 3RD SUMMER COURSE IN LANGKAT - Robert Tua Siregar; Ira Modifa; Puji Syukran; Despaleri Perangin-Angin (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Mangrove ecosystems have a crucial role as coastal fortresses as well as supporting the ecological and economic balance of the community. As a tangible manifestation of the implementation of the Tri Dharma of Higher Education, the Center for Excellence in Science and Technology (PUI) of the University of North Sumatra in synergy with Universitas Prima Indonesia held a 3rd Summer Course with the theme "International Community Service for Conservation and Mangrove Ecosystem Service". This international community service activity was held on September 6-7, 2025 in the Mangrove Forest of Beras Basah Village, Lalat Regency. The programme involves multidisciplinary and cross-border collaboration, bringing together experts and students from renowned global institutions, including Dilliman College, Chulalongkorn University (Thailand), Universiti Sultan Zainal Abidin (Malaysia), as well as the National Research and Innovation Agency (BRIN). PUI Bina Ruang UNPRI also actively participates in conducting in-depth observations on the correlation between the preservation of mangroves and the spatial layout of human life in coastal areas. Through a participatory and educational approach, this activity not only aims to accelerate environment-based national development, but also formulate innovative solutions in maintaining mangrove ecosystem services for global sustainability.